Cataract surgery outcomes in adult patients with Down's syndrome - Li, Emmy Y; Chan, Tommy C; Lam, Nai Man; Jhanji, Vishal (British journal of ophthalmology, 2014)
Purpose To describe the outcomes of cataract surgery in adult patients with Down's syndrome at a tertiary eye hospital in Hong Kong. Methods Retrospective case-file analysis was performed to identify patients with Downs's syndrome who underwent cataract surgery between January 2002 and December 2012. Morphology of cataract, associated ocular features and surgical and visual outcomes were analysed. Results Cataract surgery was performed in 33 eyes of 20 patients (12 males, 8 females, mean age 42.9±10.6 years) over a 10-year period. Nine patients (9/20, 45.0%) had bilateral cataracts at the time of diagnosis. White cataracts were noted in 12 eyes of 10 patients (12/33, 36.3%) at the time of presentation. Associated ocular problems included myopic maculopathy (18 eyes, 54.5%), keratoconus (12 eyes, 36.3%), nystagmus (2 eyes, 6.0%), corneal scar (2 eyes, 6.0%) and glaucoma (2 eyes, 6.0%). Five eyes (15.1%) underwent extracapsular cataract extraction whereas a phacoemulsification was performed in 28 (84.9%) eyes. Intraocular lens implantation was performed in 32/33 eyes. The most common postoperative complication was posterior capsular opacification (8 eyes, 24.2%). The mean best-corrected visual acuity improved from 0.07±0.11 preoperatively to 0.17±0.19 at 3 months postoperatively (p=0.000). Conclusions A high incidence of bilateral cataracts as well as white cataracts was observed in patients with Down's syndrome in our study. Although the surgical outcomes of cataract surgery were good, the visual outcomes were suboptimal in our cases due to associated ocular comorbidities.